ANALYSIS OF “IT IS HARD TO BE HUMAN” (ODAM BO‘LISH QIYIN) - Ne’matjonova, Gulyora; Djabbarova , Nilufar; Murodova , Mukaddas (Educational Research in Universal Sciences, 2023)
“It is hard to be human” (Odam bo‘lish qiyin) - Written by the People’s Writer of Uzbekistan Olmas Umarbekov. In this work there is a true breath of life. The work is the writer’s first novel, written in 1969. The simplicity of the language and the vividness of the events are noteworthy. Olmas Umarbekov has a special role in the development of Uzbek prose in the second half of the last century. His novel "It’s Hard to Be a human" is one of the most widely read works written about youth life, spiritual and moral problems, complex human relationships. The main idea of ​​the work is to explain to the reader concepts such as the fact that not everyone can preserve their loyalty to such a great feeling as love, not to be deceived by the deceitful feelings of the world, and most importantly, never to bow to the ego.